2020
DOI: 10.1021/acscentsci.0c00083
|View full text |Cite
|
Sign up to set email alerts
|

Reprocessing Postconsumer Polyurethane Foam Using Carbamate Exchange Catalysis and Twin-Screw Extrusion

Abstract: Cross-linked polyurethane (PU) is extensively used as thermoset foam; however, methods to directly reprocess PU foam waste derived from commercial sources into similar value materials have not been developed. We demonstrate that introducing dibutyltin dilaurate (DBTDL) into cross-linked PU foams and films enables their reprocessing at elevated temperatures via dynamic carbamate exchange reactions. Both model and commercial cross-linked PU foams were continuously reprocessed using twin-screw extrusion to remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(153 citation statements)
references
References 53 publications
(63 reference statements)
3
129
0
Order By: Relevance
“…Alternatively, the dynamic nature of the carbamate linkage has been exploited to enable reprocessing of PUs via catalysts familiar in PU polymerizations, namely tertiary amines, Lewis acids, and organotin compounds. [ 33–39 ] In a similar vein, polyhydroxyurethanes can be reprocessed through catalyst‐free exchange of hydroxyl and carbamate functionalities. [ 40–44 ] However, reprocessing of PUs and polyhydroxyurethanes also requires high temperature and/or extended reaction times.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the dynamic nature of the carbamate linkage has been exploited to enable reprocessing of PUs via catalysts familiar in PU polymerizations, namely tertiary amines, Lewis acids, and organotin compounds. [ 33–39 ] In a similar vein, polyhydroxyurethanes can be reprocessed through catalyst‐free exchange of hydroxyl and carbamate functionalities. [ 40–44 ] However, reprocessing of PUs and polyhydroxyurethanes also requires high temperature and/or extended reaction times.…”
Section: Methodsmentioning
confidence: 99%
“…Covalent adaptive networks (CANs) are polymer networks that contain exchangeable covalent bonds [ 139 , 140 , 141 ]. A subcategory of CANs, known as vitrimers, is particularly attractive as reprocessable and recyclable materials for AM.…”
Section: Advances In the Design Of Novel Materials For Ammentioning
confidence: 99%
“… 15 Here, possible catalyst degradation complicates the system, and the dissociative nature of the carbamate bonds indicates that the dissociated isocyanate group can be susceptible to water attack at high temperature. 16 18 Disulfide exchange is also a fast reaction that does not require any catalyst, and the system also benefits from the radical-assisted dissociative mechanism. 19 21 Nevertheless, in the past, we found that this type of xLCE suffers from oxidative side reaction at temperatures above 170 °C with sample tarring, which prevents the xLCE from multiple recycling.…”
Section: Introductionmentioning
confidence: 99%